THE PEMBERIAN SESAJEN SEBAGAI EKSPRESI SPIRITUAL SEBAGAI KONTEKS KELUARGA BAHAGIA PERSFEKTIF ALQURAN DAN HADIS - nurfadhilah syam (Al-Kauniyah: Jurnal Ilmu Al-Qur'an dan Tafsir, 2023)
This research adopts a qualitative approach to evaluate the offering of sesajen as a spiritual expression within the context of a happy family, referencing the perspectives of the Quran and Hadith. The study investigates the impact of sesajen practices on family happiness and the potential for actions considered as shirk from a religious standpoint. Through in-depth interviews with involved family members and analysis of relevant Quranic and Hadith texts, it was found that the practice of sesajen does not significantly contribute to family happiness and, in some cases, can lead to disharmony. The Quranic perspective emphasizes the importance of sincerity in worship, while Hadith highlights the significance of sacrifice and affection in the family context. Additionally, a perspective emerged suggesting that sesajen may reflect acts of shirk, surpassing the limits of worship solely to Allah. Although this view is not uniform, it reveals diversity in interpretation. Consequently, within the framework of Quranic and Hadith perspectives, the practice of sesajen needs evaluation concerning family happiness and compatibility with fundamental religious values.